2013
DOI: 10.1128/jvi.00270-13
|View full text |Cite
|
Sign up to set email alerts
|

Orchid Fleck Virus Structural Proteins N and P Form Intranuclear Viroplasm-Like Structures in the Absence of Viral Infection

Abstract: bOrchid fleck virus (OFV) has a unique two-segmented negative-sense RNA genome that resembles that of plant nucleorhabdoviruses. In infected plant cells, OFV and nucleorhabdoviruses induce an intranuclear electron-lucent viroplasm that is believed to be the site for virus replication. In this study, we investigated the molecular mechanism by which OFV viroplasms are produced in vivo. Among OFV-encoded proteins, the nucleocapsid protein (N) and the putative phosphoprotein (P) were present in nuclear fractions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…7b in Martin et al, 2012). In this study, interaction between ADV N and P was also demonstrated by BiFC, where the location of the N:P complex was subnuclear, similar to that reported for SYNV, PYDV, CoRSV and OFV (Bandyopadhyay et al, 2010;Min et al, 2010;Kondo et al, 2013;Ramalho et al, 2014), but different to that observed for LNYV, which was in the cytoplasm . The BiFC results for ADV N and P proteins confirmed the earlier observed co-localization results for these proteins, and showed that the interaction was similar to that reported for these two proteins from nucleorhabdoviruses rather than cytorhabdoviruses.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…7b in Martin et al, 2012). In this study, interaction between ADV N and P was also demonstrated by BiFC, where the location of the N:P complex was subnuclear, similar to that reported for SYNV, PYDV, CoRSV and OFV (Bandyopadhyay et al, 2010;Min et al, 2010;Kondo et al, 2013;Ramalho et al, 2014), but different to that observed for LNYV, which was in the cytoplasm . The BiFC results for ADV N and P proteins confirmed the earlier observed co-localization results for these proteins, and showed that the interaction was similar to that reported for these two proteins from nucleorhabdoviruses rather than cytorhabdoviruses.…”
Section: Discussionsupporting
confidence: 81%
“…The interaction of N and P proteins is a common feature among not only the already characterized LNYV , PYDV (Bandyopadhyay et al, 2010) and SYNV (Min et al, 2010) but also the recently characterized dichorhaviruses coffee ringspot virus (CoRSV) (Ramalho et al, 2014) and orchid fleck virus (OFV) (Kondo et al, 2013), which have bipartite, negative-strand RNA genomes with clear sequence similarities to those of nucleorhabdoviruses, and the vertebrate rhabdovirus, vesicular stomatitis virus (VSV) (Moerdyk-Schauwecker et al, 2009; Fig. 7b in Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MFSV N and P proteins co-localize in the nucleolus (Tsai et al, 2005) and PYDV N and P form large sub-nuclear aggregates (Bandyopadhyay et al, 2010;Martin et al, 2012). OFV and CoRSV N and P proteins interact and form large sub-nuclear foci with CoRSV N and P also co-localised throughout the cell (Kondo et al, 2013;Ramalho et al, 2014). The nuclear viroplasm-focussed N and P protein interaction and co-localization seen for dichorha-and nucleorhabdoviruses is in stark contrast to the co-localization and interaction of cytorhabdovirus N and P proteins in the cytoplasm outside the nucleus (Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 76%
“…P proteins of OFV and CoRSV are also exclusively nuclear (Kondo et al, 2013;Ramalho et al, 2014). For all nucleorhabdoviruses where viral protein localization and interactions have been studied, N and P proteins have been shown to interact and co-localize in the nucleus (Goodin et al, 2001(Goodin et al, , 2002Tsai et al, 2005;Bandyopadhyay et al, 2010;Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation